Penalaran Deduktif Siswa Dalam Menyelesaikan Masalah Matematika Hots Yang Memiliki Tingkat Efikasi Diri Rendah - Yunita Nailul Fajriyah; Syaiful Hadi (Journal of Education and Learning Sciences, 2023)
Mathematical deductive reasoning is a conclusion based on agreed rules and the conclusions are general to specific conclusions. Meanwhile, math problems based on High Order Thinking Skill (HOTS) are problems that require students to be able to argue and solve problems and understand something more clearly. Self-efficacy is an individual's belief in determining and completing an action. The purpose of this study was to determine students' mathematical deductive reasoning abilities in solving HOTS math problems if they had low self-efficacy. This research was conducted at MTSN 3 Blitar. Data collection was carried out using questionnaires, tests and interviews. Data analysis techniques using analysis qualitative data which includes data reduction, data presentation and interesting conclusion/verification. Based on the initial results of the study the results obtained students with a low level of self-efficacy in solving HOTS math problems, namely fulfilling two indicators of mathematical deductive reasoning abilities, namely being able to write down existing data or information and write down the data or information asked